EFFECTS OF PROBIOTICS ON LIPID PROFILES IN HYPERCHOLESTEROLEMIA ADULT PATIENTS: AN EVIDENCE-BASED CASE REPORT - Elisa; Wiji Lestari (Perhimpunan Dokter Gizi Klinik Indonesia, 2021)
Background: Hypercholesterolemia prevalence was 39% in adults and a risk factor for cardiovascular, cerebrovascular, atherosclerotic disease, leading to vertigo. Diet and specific food potentiate in dyslipidemia risk reduction. Several studies have been proposed that probiotics have a hypocholesterolemic effect. Objectives: This study aims to determine the effect of probiotics on lipid profiles in hypercholesterolemia adult patients. Methods: Electronic literature searching was conducted from Pubmed, Scopus, and Cochrane Library. MeSH Terms combined with Title/Abstract are used in advanced search based on inclusion and exclusion criteria. Results: Critical appraisal was conducted for a systematic review and meta-analysis of randomized controlled trials. Probiotic supplementation significantly decreases total cholesterol and low-density lipoprotein cholesterol levels but not statistically significant in high-density lipoprotein and triglycerides levels. Conclusion: Single strain Lactobacillus plantarum probiotics for at least six weeks can improve total cholesterol levels in hypercholesterolemia adult patients.